Factor structure and equivalence of maternal resources for care in Bangladesh, Vietnam, and Ethiopia - Basnet, Sulochana; Frongillo, Edward A.; Nguyen, Phuong Hong; Moore, Spencer; Arabi, Mandana (Springer, 2021)
Resources for care among women are crucial for children’s growth and development. The objectives of this cross-sectional study were to determine if: (1) the factor structure of measures of maternal resources for care was comparable across countries and consistent with the theoretical constructs and (2) the measures showed equivalence across contexts.The study included 4400, 4029 and 2746 women from Bangladesh, Vietnam, and Ethiopia, respectively. The measures of resources for care were maternal education, knowledge, height, body mass index, mental well-being, financial autonomy, decision-making, employment, support in chores, and perceived support.The factor analysis demonstrated that a two-factor solution best explained the structure of resources for care in all three countries. The first factor was associated with financial autonomy and employment in all three countries and with decision-making in two countries. The second factor was associated with education and knowledge in all three countries. The measures of resources for care had measurement equivalence across countries.Resources for care were structurally similar and measurement equivalent across countries and can be used for measurement in low- and middle-income countries. Additional work examining the structure and cross-context equivalence of resources for care in other settings is warranted.